Hand injuries in south Wales coal miners. - Morgan, W J (1985)
Fifty eight coal miners attended the Royal Gwent Accident and Emergency Department with serious hand injuries over a three year period. The commonest cause of the injuries was falling rock or coal from the pit roof crushing the hand and the commonest type of injury was the crushed, compound fracture of the terminal phalangeal area of the digit, with or without pulp loss. Records of the time off work with the injury were obtained in 52 miners. Only seven (13%) returned to work within one month. Of 40 individual distal phalangeal injuries reviewed after one year, only four (10%) had normal sensation and full movement at the distal joint. Nevertheless, only seven miners (13%) had to alter their initial occupation at the mine and move to lighter duties.